Growth, employment and the standard of living in selected Commonwealth Caribbean countries. - RAMSARAN, Ramesh (1992)
Examines the nature and size of the unemployment problem. Presents information on recent trends in the standard of living. Concludes that the persistent high level of unemployment, and the difficulties facing Governments in the region in providing adequate housing, health and education facilities, seem to indicate that the population growth rate may still be too high.